PERANAN Anopheles barbirostris VANDER WULP SEBAGAI PENULAR PENYAKIT - Hasan Boesri (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2011)
An. barbirostris is one of mosquito of the genus Anopheles and was classified as 23-57 old days. It can be found at rice fields and swamps at an altitude of 2770 meters above sea level. The most preferred habitat is fresh water and pH 6-7. It is anthropolophilic and endophilic. This species in some areas, especially in East Nusa Tenggara role in transmitting malaria and filariasis.